Assessment of the sedimentation rate of the suspended matter in the surface layer of the water mass in the Bransfield Strait (Western Antarctica) using 234Th as a natural radiotracer - S. B. Gulin; E. Z. Samyshev; N. A. Stokozov; A. A. Sysoyev (Ukrainian Antarctic Journal, 2003)
Measurements of particulate and dissolved 234Th have been carried out in the surface waters across the Bransfield Strait. The disequilibrium discovered between concentrations of the total 234Th and its soluble long-lived mother radionuclide – 238U has allowed an evaluation of particle fluxes in the euphotic zone. The highest flux was found in a mixing zone of waters coming from the Bellingshausen Sea and the Weddell Sea. Total particle fluxes from the upper 150-m water column are estimated of about 2.2 g·m-2·day-1 in the eastern part of the Strait and 3.1 g·m-2·day-1 in the western area. Residence time of the sinking particles in the upper 150 m is assessed to be in the range of 105 to 120 days, which corresponds with the duration of spring-summer months when the Strait is free from the ice cover limiting of the development of phytoplankton assemblages.